The effect of thickness of a conductive nanocomposite ink printed on textile co-planar waveguide antenna - Mohd Radi, Nor Hadzfizah; Ismail, Mohd Muzafar; Zakaria, Zahriladha; Razak, Jeefferie Abd (Bulletin of Electrical Engineering and Informatics, 2024)
In the area of wearable technology an enhancement of basic microstrip antenna is evolution of wearable textile antenna. A new development of wearable antenna is the incorporated of conductive plane using nanocomposite ink that embedded onto the fabric. In this paper, the performance of variety thickness of conductive Graphene-Ag-Cu ink on a drill fabric is presented. The performances include its resistivity and conductivity measurement. By performing a measurement using scanning electron microscopy, energy-dispersive X-ray spectroscopy, and four-point probe, it can obtain and measure the composition and thickness of nanocomposite layered on a fabric and resistivity respectively. Hence, it can provide detailed information about the surface morphology, roughness, and thickness of the nanocomposite coating on the fabric as well as the electrical conductivity. Finally, the electrical conductivity increased to the fifth layered from 0.1473×104 S/cm up to 0.5393×104 S/cm.